The Influence Of Product And Service Quality On Consumer Satisfaction At Burger King In Bandar Lampung - Vio Prakusya Oestabima; Vonny Tiara Narundana (Cita konsultindo, 2024)
Burger King Bandar Lampung encountered a problem, namely, Burger King sales data in Bandar Lampung experienced sales instability, as evidenced by fluctuations in Burger King Bandar Lampung sales revenue. The purpose of this study was to see how product quality and service quality affected consumer satisfaction at Burger King in Bandar Lampung. The sample in this study is made up of 100 Burger King customers. A questionnaire was used to collect data. SPSS version 25 with valid and reliable status is used to test the validity and reliability of research. According to the findings of this study, product quality and service quality both influence consumer satisfaction.